Climatic adaptation of social housing districts in an arid city: Piura - Caldas, Patricia (2019)
This interdisciplinary study evaluates the possibilities of urban adaptation of an arid city, specifically neighborhoods of social housing, in the face of climate change. The city of Piura was selected because it is one of the most representative cases of the effects of climate change in an arid city of the country with problems of water scarcity and it is analyzed: a) its territorial development in relation to water problems, b) the impact of urbanization processes on the urban heat islands of Piura; and c) possible measures for climate adaptation of public space and housing in neighborhoods of social interest. The results on the institutional framework of the planning for the climatic adaptation of this city show more obstacles than opportunities. In both neighborhoods selected case studies are confronted urban design and architecture with "popular" adaptation interventions and the socio-economic profile of residents is studied to understand patterns and measures to be considered in processes of climate adaptation. Finally, participatory adaptation strategies that reduce heat islands in the public space and social housing in Piura are conceptualized within the framework of comprehensive public policies.